KUALITAS PELAYANAN PEMBAYARAN PASIEN UMUM PADA KASIR RUMAH SAKIT UMUM DAERAH (RSUD) CARUBAN KABUPATEN MADIUN - Maryani, Sri; Suwardi, Suwardi; Sardjono, Herning Suryo (Master of Public Administration, Universitas Slamet Riyadi, 2024)
ABSTRACT THE QUALITY OF PUBLIC PATIENT PAYMENT SERVICES AT CASHIER OF REGIONAL PUBLIC HOSPITAL (RSUD) CARUBAN MADIUN REGENCY Public service is an effort of state to fulfill the basic needs and rights of its citizens. Public service providers must stick to the principle of excellent service. RSUD Caruban in Madiun Regency is one of the public service providers in health sector. One of the non-medical service units in RSUD Caruban is cashier's payment service. However, there are still complaints from patients about the quality of the service. The purpose of this study is to analyze the quality of public patient payment services at the cashier of RSUD Caruban, Madiun Regency which was measured on five service dimensions, namely Tangibles, Responsiveness, Reliability, Assurance, and Empathy. This research was carried out at the RSUD Caruban, Madiun Regency. The population was all public patients at RSUD Caruban in Madiun Regency or their representative families. The sample was determined by Accidental sampling using Lemeshow formula, 96 people. Source of data consists of primary data and secondary data. Data collection techniques of this study using a questionnaire. Data were analyzed descriptively quantitatively with the help of frequency tables. The results of the study showed that the quality of public patient payment services at cashier of regional public hospital (RSUD) Caruban Madiun Regency is good. It is supported by average score result of 5 dimensions of the service. The first, the total average score of Tangibles is 3,86 which is included in good quality category. second, the total average score of Responsiveness is 4,14 which is included in good quality category. Third, the total average score of Reliability is 4,10 which is included in good quality category. Fourth, the total average score of Assurance is 4,17 which is included in good quality category. And fifth, the total average score of Empathy is 4,12 which is included in good quality category. Keywords: Service Quality, Tangibles, Responsiveness, Reliability, Assurance, Empathy